Emergence of Dirac-like bands in the monolayer limit of epitaxial Ge films on Au(1 1 1). (13th July 2017) - Schröter, Niels B M; Watson, Matthew D; Duffy, Liam B; Hoesch, Moritz; Chen, Yulin; Hesjedal, Thorsten; Kim, Timur K
Abstract: After the discovery of Dirac fermions in graphene, it has become a natural question to ask whether it is possible to realize Dirac fermions in other two-dimensional (2D) materials as well. In this work, we report the discovery of multiple Dirac-like electronic bands in ultrathin Ge films grown on Au(1 1 1) by angle-resolved photoelectron spectroscopy. By tuning the thickness of the films, we are able to observe the evolution of their electronic structure when passing through the monolayer limit. Our discovery may signify the synthesis of germanene, a 2D honeycomb structure made of Ge, which is a promising platform for exploring exotic topological phenomena and enabling potential applications.